STAT4‐mediated transcriptional repression of the IL5 gene in human memory Th2 cells. Issue 6 (8th April 2016) - Gonzales‐van Horn, Sarah R.; Estrada, Leonardo D.; van Oers, Nicolai S. C.; Farrar, J. David
Abstract : Type I IFN negatively regulates IL5 and IL13 gene expression in human CD4 + T cells by suppressing nascent gene transcription. This repression is mediated by STAT4 as either a homodimer, or paired with STAT1 as a heterodimer. This is the first demonstration of STAT4 acting as a transcriptional repressor. Abstract : Type I interferon (IFN‐α/β) plays a critical role in suppressing viral replication by driving the transcription of hundreds of interferon‐sensitive genes (ISGs). While many ISGs are transcriptionally activated by the ISGF3 complex, the significance of other signaling intermediates in IFN‐α/β‐mediated gene regulation remains elusive, particularly in rare cases of gene silencing. In human Th2 cells, IFN‐α/β signaling suppressed IL5 and IL13 mRNA expression during recall responses to T‐cell receptor (TCR) activation. This suppression occurred through a rapid reduction in the rate of nascent transcription, independent of de novo expression of ISGs. Further, IFN‐α/β‐mediated STAT4 activation was required for repressing the human IL5 gene, and disrupting STAT4 dimerization reversed this effect. This is the first demonstration of STAT4 acting as a transcriptional repressor in response to IFN‐α/β signaling and highlights the unique activity of this cytokine to acutely block the expression of an inflammatory cytokine in human T cells.